Management Care Midwifery Family Planning on Ny "F " DMPA Injecting KB Acceptor with Enhancement Weight at RSIA Happy Makassar in 2022 - Fitriana Jufri P; Surmayanti Surmayanti (Jurnal EduHealth, 2023)
The population from year to year has increased relatively high and not balanced. This resulted in heavy pressure from various sectors of the provision of clothing, food, employment, education, health and others. The government is handling it by making a program, namely Family Planning (KB) to control the rate of population growth. DMPA injection birth control is a method of birth control that is very effective in preventing pregnancy. type of research is a case study by carrying out Midwifery Family Planning Care Management on Ny. "F" DMPA injecting family planning acceptors with increased body weight at RSU Bahagia Makassar in 2022 according to Varney and SOAP's 7 steps. The diagnosis of Ny "F" was enforced by subjective data, there were complaints of increasing body weight while being a DMPA injectable KB acceptor and objective data was obtained by mothers using DMPA injecting KB. It is known that the increase in body weight experienced by Mrs. "F" is a physiological matter for users of DMPA injection KB with counseling so that the mother no longer feels anxious and worried about her condition From these cases, what can be taken is that basic data collection, diagnosis and action identification have been carried out for Mrs. "F" in accordance with the DMPA injection family planning acceptor case with increased body weight. You understand that weight gain is a side effect of using DMPA. Another important thing is that the mother understands that Islam advocates efforts to improve the quality of the family, including through family planning